Mediare conflitti o resistere alla crisi? Servizio civile all’estero, tra “Obiezione di coscienza” e “Garanzia giovani” - Sebastiano Miele (EtnoAntropologia)
In line with the Conscientious Objection, the Voluntary Civilian Service (Italian Law 64/2001) comes as a means of Civil disobedience and nonviolent defence. It aims to promote solidarity, cooperation and education to peace through the mediation of the conflicts. Lately it’s becoming to be rather perceived as a means of countering the youth unemployment and "staff shortages" of different institutions. After a brief historical overview, the paper focuses the analysis on people recently holding their Service abroad. Special attention is devoted to a sort of anthropological dimension that seems positively characterize this experience in recent years.